2016
DOI: 10.1021/jacs.5b12790
|View full text |Cite
|
Sign up to set email alerts
|

Rh2(II,III) Catalysts with Chelating Carboxylate and Carboxamidate Supports: Electronic Structure and Nitrene Transfer Reactivity

Abstract: Dirhodium-catalyzed C-H amination is hypothesized to proceed via Rh2-nitrene intermediates in either the Rh2(II,II) or Rh2(II,III) redox state. Herein, we report joint theoretical and experimental studies of the ground electronic state (GES), redox potentials, and C-H amination of [Rh2(II,III)(O2CCH3)4(L)n](+) (1_L) (L = none, Cl(-), and H2O), [Rh2(esp)2](+) (2), and Rh2(espn)2Cl (3) (esp = α,α,α',α'-tetramethyl-1,3-benzenedipropanoate and espn = α,α,α',α'-tetramethyl-1,3-benzenedipropanamidate). CASSCF calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 103 publications
(169 reference statements)
2
68
0
Order By: Relevance
“…The effect of the counteranion on selectivity was minimal, suggesting it is not bound to Ag during the key bond-forming event. 17e,i,21 Counteranion-free Ag-nitrene species were also supported by computational studies (vide infra). 17e,i Concentration had little effect on selectivity, while decreasing the temperature from +25 to −20 °C improved the 2:3 ratio.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The effect of the counteranion on selectivity was minimal, suggesting it is not bound to Ag during the key bond-forming event. 17e,i,21 Counteranion-free Ag-nitrene species were also supported by computational studies (vide infra). 17e,i Concentration had little effect on selectivity, while decreasing the temperature from +25 to −20 °C improved the 2:3 ratio.…”
Section: Resultsmentioning
confidence: 72%
“…13 However, computational studies carried out by Berry and Musaev showed that a requirement for concerted nitrene transfer is the presence of an empty N-centered orbital on the metal−nitrene intermediate. 21 The triplet ground states of Ag−nitrene intermediates do not permit this condition to be met; thus, reactions catalyzed by Ag(tpa)OTf are electronically prohibited from occurring via concerted pathways. Further computational modeling resolved this discrepancy by showing that Ag-catalyzed NT can proceed via a mechanism we have termed “elementary hydrogen transfer/radical recombination” (E-HT:RR).…”
Section: Resultsmentioning
confidence: 99%
“…In concerted insertions of nitrenes into C‒H bonds, as is seen in Rh 2 -catalyzed reactions, the transition state involves simultaneous (though asynchronous) C-N and N-H bond formation and C‒H cleavage. 18 These three interactions take place within a triangular, three-membered ring transition state (left, Scheme 6). Stepwise reactions proceed first through a hydrogen atom transfer (HAT) transition state leading to radical intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the electric charge (about 1.04 e) of central Rh 2+ is remarkably underestimated, whereas covalence and the strength of local crystal fields around Rh are overestimated, leading to the calculation errors for the resultant g tensor . Meanwhile, the two‐fold orbital degenerated ground 2 E g state for octahedral 4d 7 (Rh 2+ ) centers can induce extra errors in the DFT calculations . Second, LDA is found to be the best choice in all functionals for both g and A tensors.…”
Section: Resultsmentioning
confidence: 98%